Color-coded imaging of electrochromic process at single nanoparticle level - Jing, Chao (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Electrochromic materials have attracted increasing attention in the field of smart devices and energy economy due to their excellent reversible chromic properties. Investigating an electrochromic process at the nano-scale is beneficial to the development of functional nano-devices exploiting chromophores. In this study, a new method for real-time imaging of an electrochromic process at the single nanoparticle level is developed based on an ultra-sensitive plasmon resonance energy transfer (PRET) technique. The scattering light intensity of nanoparticles is applied to reveal energy transfer from nanoparticles to chromophores modulated by an electrochromic reaction. This PRET-based technique achieves the detection of hundreds of molecules on the surface of a single nanoparticle. Furthermore, a color-coded amplifying method has been introduced for high-throughput, converting light intensity into easily recognized colors via the Matlab program. Compared with traditional electrochemical imaging techniques, this facile and rapid approach using optical techniques to characterize a real-time electrochemical process significantly enhances detection sensitivity, time and spatial resolution. Notably, the obtained electrochromic behavior of chromophores on a single nanoparticle is in good agreement with the simulated cyclic voltammetry (CV) curves on a nano-electrode. Therefore, this study provides a promising way to simultaneously monitor electrochromic reactions on single nano-electrodes with high-throughput.